The West African monsoon dynamics, Part I : Intra-seasonal variability - (:unkn) unknown (My University, 2003)
Intraseasonal variability in the West African monsoon is documented by using daily gridded datasets of rainfall and convection, and reanalyzed atmospheric fields, over the period 1968-90. Rainfall and convection over West Africa are significantly modulated at two intraseasonal timescales, 10-25 and 25-60 day, leading to variations of more than 30% of the seasonal signal. A composite analysis based on the dates of the maximum (minimum) of a regional rainfall index in wet (dry) sequences shows that these sequences last, on average, 9 days and belong to a main quasiperiodic signal of about 15 days. A secondary periodicity of 38 days is present but leads to a weaker modulation. During a wet (dry) sequence, convection in the ITCZ is enhanced (weakened) and its northern boundary moves to the north (south), while the speed of the African easterly jet decreases (increases), the speed of the tropical easterly jet increases (decreases), and the monsoon flow becomes stronger (weaker), all these features being similar to the ones associated with interannual variability characterizing wet and dry years. This modulation of convection at intraseasonal timescales is not limited to West Africa but corresponds to a westward-propagating signal from eastern Africa to the western tropical Atlantic. An enhanced monsoon phase is associated with stronger cyclonic activity in the low levels over the Sahel associated with stronger moisture advection over West Africa. Five days before the full development of the wet phase, a stronger cyclonic circulation at 20ЊE induces enhanced southerly winds along 25ЊE where convection enhances, while another westwardpropagating cyclonic circulation is located at 0Њ. This atmospheric pattern is linked to the enhancement of the subsiding branch of the northern Hadley cell at 35ЊN, northerly advection of drier air over West Africa, and to increased dry convection in the heat low at 20ЊN. It propagates westward, leading to a zonally extende
Keywords: African Research